TEORI MODERNISASI DALAM EKONOMI POLITIK; ANALISIS FAKTOR KETERBELAKANGAN EKONOMI INDONESIA DALAM PERBANDINGAN DENGAN KOREA SELATAN - Fathimah Syirin (Cahaya Ilmu Bangsa, 2025)
Indonesia and South Korea have contrasting economic trajectories despite their differences in natural resources. Indonesia, rich in natural resources, has not fully capitalized on its potential, while South Korea, with fewer resources, has emerged as a leading economic power. This study focuses on the role of human resources and policy in shaping these disparities, using modernization theory within political economy as the analytical lens. The research employs a qualitative comparative method, analyzing human capital development, economic policies, and institutional structures of both nations. Findings show that South Korea’s success is largely attributed to investments in human capital, education, and consistent, long-term economic policies that foster industrial growth. In contrast, Indonesia’s underdevelopment stems from challenges in education, weak institutional frameworks, and inconsistent policy implementation. The study concludes that Indonesia must focus on improving its human resources through better education, stronger institutions, and more coherent policies to harness its natural resources effectively and stimulate sustained economic growth.